2017
DOI: 10.1002/eqe.2892
|View full text |Cite
|
Sign up to set email alerts
|

Collapse risk of controlled rocking steel braced frames with different post‐tensioning and energy dissipation designs

Abstract: Summary Controlled rocking steel braced frames (CRSBFs) are low‐damage self‐centring lateral force resisting systems. Previous studies have shown that designing the energy dissipation (ED) and post‐tensioning (PT) in CRSBFs using a response modification factor of R=8 can prevent collapse of structures during earthquakes beyond the design level. However, designers have unique control over the hysteretic behaviour of the system, even after the response modification factor is selected. Additionally, recent studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The design methodology set out by Wiebe and Christopoulos 27 was used to design the base rocking joints of the CRBFs based on selected values for the response modification factor R, the energy dissipation ratio β (see Figure 1), and the fundamental period of the CRBF before uplift. Each design was commenced using R = 8, as recommended by several researchers, 2,3,28 but this value was sometimes increased to achieve the same drift demands as in the BRBF designs, as discussed subsequently, based on other studies showing that CRBFs can meet drift and collapse criteria with larger values of R. 27,29 Two different values of β (25% and 90%) were used for each building height, as listed in Table 1, in order to assess the influence of this parameter on the demands on nonstructural components. The ratio of the initial stress of the prestressing to the ultimate stress of the prestressing was targeted to be η = 15% for all CRBF designs, although this design objective needed to be altered for the 12-story CRBFs, as discussed later.…”
Section: Controlled Rocking Braced Framesmentioning
confidence: 99%
“…The design methodology set out by Wiebe and Christopoulos 27 was used to design the base rocking joints of the CRBFs based on selected values for the response modification factor R, the energy dissipation ratio β (see Figure 1), and the fundamental period of the CRBF before uplift. Each design was commenced using R = 8, as recommended by several researchers, 2,3,28 but this value was sometimes increased to achieve the same drift demands as in the BRBF designs, as discussed subsequently, based on other studies showing that CRBFs can meet drift and collapse criteria with larger values of R. 27,29 Two different values of β (25% and 90%) were used for each building height, as listed in Table 1, in order to assess the influence of this parameter on the demands on nonstructural components. The ratio of the initial stress of the prestressing to the ultimate stress of the prestressing was targeted to be η = 15% for all CRBF designs, although this design objective needed to be altered for the 12-story CRBFs, as discussed later.…”
Section: Controlled Rocking Braced Framesmentioning
confidence: 99%
“…Based on previous relevant research [22,23,43], it was hypothesized that by maximising the energy dissipation at the column bases, the seismic response and collapse capacity of the SC-MRF-CBs would be optimally improved. Because the upper bound of βE equals 0.5 [25,42], βE was conservatively taken equal to 0.48 in all self-centering column bases.…”
Section: Investigated Base Structural Propertiesmentioning
confidence: 99%
“…The system-level and the record-to-record uncertainty were used for the construction of the fragility curves. The FEMA P695 [59] regulations were used for the calculation of the total uncertainty, where additional system-level uncertainty were added from three categories [43]. The total uncertainty of the system, βTotal, is given by:…”
Section: Collapse Assessmentmentioning
confidence: 99%
“…Three-dimensional analysis models were used to evaluate explicitly include the vertical response of the roof and floor beams framing into G-RCBFs. Fragility curves developed for PT-CRBFs in previous studies [12,13] have shown that the system can exhibit satisfactory seismic performance when designed with R factors in the order of 8. For G-CRBFs, in absence of PT strands, collapse by overturning could represent a concern in design and fragility curves were therefore generated for the frames studied to evaluate the margins they offered against this ultimate limit state.…”
Section: Introductionmentioning
confidence: 99%